Small change, big impact: the shape of precursor polymers governs poly-p-phenylene synthesis - Abdulkarim, Ali; Strunk, Karl-Philipp; Bäuerle, Rainer; Beck, Sebastian; Makowska, Hanna; Marszalek, Tomasz; Pucci, Annemarie; Melzer, Christian; Jänsch, Daniel; Freudenberg, Jan; Bunz, Uwe H. F.; Müllen, Klaus (Macromolecules, 2019)
The synthesis of unsubstituted, structurally perfect poly(para-phenylene) (PPP) has remained elusive for many decades. By modifying our previously reported precursor route towards PPP, we were able to simplify and optimize the precursor polymer synthesis and yields, the thermal conversion process to PPP, and the resulting material properties. We describe the synthesis of unprecedented anti-dialkoxycyclohexadienylenes, polymerized via Suzuki coupling to yield linear PPP precursor polymers. Changing the geometry and overall shape of the precursor viz upon going from syn- to anti-configuration of the monomer has two important consequences: (i) formation of the precursor polymer becomes more selective since cyclization of the monomer is no longer possible and (ii) the precursor polymer adopts a "stretched" geometry and becomes more similar to the rigid-rod of PPP, impacting the aromatization process and material properties. Films of the precursor polymers are thermally aromatized via dealkoxylation to yield structurally perfect and highly ordered, insoluble PPP. Long-range ordering within the thin films, not observed for its syn-analog, is induced as evidenced by atomic force microscopy, X-ray scattering, and IR and UV-vis/photoluminescence spectroscopy. The aromatization temperature, now feasible for fabrication of plastic devices, is significantly lowered from previously reported 300 degrees C to below 250 degrees C. The kinetics of the aromatization process were monitored via time-dependent IR measurements at different annealing temperatures, showing much faster quantitative aromatization for thin layers.